Variedades de cana-de-açúcar tolerantes ao déficit hídrico - Silverio, Janaina de Miranda (2016)
This study aimed to identify varieties of sugarcane tolerant to drought for Mato Grosso cerrado through the biometric characteristics, stomatal conductance and proline concentration. The design was a randomized block, composed of seven varieties, two standards considered tolerant (RB867515, RB92579) and two standards considered susceptible to water stress (RB855536 and RB72454) and three clones (RB073036, RB073028 and RB073040), respectively, five water tension as the absence of water deficit (12 kPa) and moderate drought 24 kPa, 36 kPa) and severe water deficit (48 kPa and 60 kPa), respectively, were maintained until the end of the experiment at 90 days after transplanting (DAT) in pots in the greenhouse, with three replications. Evaluations were made 30 DAT 60 and 90, respectively, such as biometrics, stomatal conductance and proline. The RB867515 variety along the water stress imposition time showed the highest values and smaller reductions in severe water deficit in diameter culms. The RB92579 variety in leaf number stands along imposition of water stress. The RB867515 variety shows minor reductions in volume root and has proline accumulation in higher water and correlated deficit with the lowest income losses in severe stress over time, and may consider it as tolerant to severe stress. The RB92579 variety has the smallest losses in volume root and stomatal conductance and has proline accumulation in higher water and correlated deficit with the lowest income losses in moderate stress, and may consider it as tolerant to moderate stress. The RB72454 variety lossy volume root and has proline accumulation in higher hydric deficit by moderate stress, however with the lowest concentration that RB92579 and correlated with the largest yield loss, over time, and may regard it as sensitive to severe water stress. The RB855536 variety has the highest losses in volume root and stomatal conductance and has no accumulation of proline over water stress time and correlated with higher income losses and may consider it as sensitive to mild water stress, moderate and severe . The clone RB073028 lossy volume root and has proline accumulation in higher water deficit in moderate stress, much higher compared RB92579, over time and correlated with lower losses of income, and may consider it as tolerant to moderate stress . The clone RB073036 presents losses in root mass and volume has proline accumulation in higher water and correlated deficit with the lowest income losses in severe stress over time, and may consider it as tolerant to severe water stress. The clone RB073040 presents greater losses in root volume in water deficit and has proline accumulation in light water stress and correlated smaller income losses and may consider it as tolerant to mild water stress.